2021
DOI: 10.3791/62852-v
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography Coupled to Refractive Index or Mass Spectrometric Detection for Metabolite Profiling in Lysate-based Cell-free Systems

Abstract: Engineering cellular metabolism for targeted biosynthesis can require extensive design-build-test-learn (DBTL) cycles as the engineer works around the cell's survival requirements. Alternatively, carrying out DBTL cycles in cell-free environments can accelerate this process and alleviate concerns with host compatibility. A promising approach to cell-free metabolic engineering (CFME) leverages metabolically active crude cell extracts as platforms for biomanufacturing and for rapidly discovering and prototyping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Furthermore, ATP overproduction negatively impacts CFE efficiency . Thus, for any given protein, an optimal range of initial reaction PEP concentrations exists where PEP energizes but is not inhibitory toward TX/TL. This range is further defined by central metabolic reactions that consume ATP in an unproductive manner (i.e., not contributing to protein expression). ,, In the case of NRPS CFE, the A domain that is characteristic of these enzymes could also deplete the ATP pool, further contributing to expression limitations. , The TC/FlAsH protocol was thus tested as a potential strategy for assessing the sensitivity of BpsA expression to PEP concentrations, and for investigating whether the catalytic A domain also competes for this TX/TL resource.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, ATP overproduction negatively impacts CFE efficiency . Thus, for any given protein, an optimal range of initial reaction PEP concentrations exists where PEP energizes but is not inhibitory toward TX/TL. This range is further defined by central metabolic reactions that consume ATP in an unproductive manner (i.e., not contributing to protein expression). ,, In the case of NRPS CFE, the A domain that is characteristic of these enzymes could also deplete the ATP pool, further contributing to expression limitations. , The TC/FlAsH protocol was thus tested as a potential strategy for assessing the sensitivity of BpsA expression to PEP concentrations, and for investigating whether the catalytic A domain also competes for this TX/TL resource.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Contrary to the previous report ( 29 ), no formate was detected in any of the modified extracts or in the unmodified extract. PflB activity in lysates has been described in the past, so it is likely that formate was only accumulated here at undetectable levels or was actively consumed by formate dehydrogenases ( 29 , 30 , 37 ). Since it has been previously shown that LdhA and PflB can be simultaneously purified from the lysate by this procedure, decreasing lactate buildup was used as a proxy for evaluating the purification of both proteins ( 29 ).…”
Section: Resultsmentioning
confidence: 88%
“…Conventionally, for 1 mol glucose consumed, glycolysis generates 2 mol of NADH that is primarily recycled to NAD + via the lactate-forming LdhA enzyme ( Figure 1A ). Because this reaction sustains glycolysis by providing NAD + , lactate has been observed as a major fermentation product in the lysate metabolism of glucose ( 30 ). To redirect flux toward ethanol, an alternative ethanol-forming, [NAD + ]/[NADH] balancing pathway can be activated through the pyruvate dehydrogenase complex and aldehyde-alcohol dehydrogenase (PDHC–AdhE) pathway module ( 29 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations